2020
DOI: 10.1021/acs.joc.9b03108
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble NIR Absorbing and Emitting Indolizine Cyanine and Indolizine Squaraine Dyes for Biological Imaging

Abstract: Organic dyes that absorb and emit in the near-infrared (NIR) region are potentially noninvasive, high-resolution, and rapid biological imaging materials. Indolizine donor-based cyanine and squaraine dyes with water-solubilizing sulfonate groups were targeted in this study due to strong absorptions and emissions in the NIR region. As previously observed for nonwater-soluble derivatives, the indolizine group with water-solubilizing groups retains a substantial shift toward longer wavelengths for both absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 50 publications
(122 reference statements)
2
43
0
Order By: Relevance
“…SQs are attractive materials in biomedical fields due to their molecular transformation in biological environment where typically applied in cell, [ 107 ] tissue, [ 108 ] and organs [ 109 ] for tumor and cancer treatments. The SQs can be functionalized diversely by designing molecules with respect to the applications, for example, direct capture of targeted ions and polar molecules, that results in color change in range of visible and fluorescent range and electrical response.…”
Section: Squaraine‐based Functional Materials For Biomedical Applicatmentioning
confidence: 99%
“…SQs are attractive materials in biomedical fields due to their molecular transformation in biological environment where typically applied in cell, [ 107 ] tissue, [ 108 ] and organs [ 109 ] for tumor and cancer treatments. The SQs can be functionalized diversely by designing molecules with respect to the applications, for example, direct capture of targeted ions and polar molecules, that results in color change in range of visible and fluorescent range and electrical response.…”
Section: Squaraine‐based Functional Materials For Biomedical Applicatmentioning
confidence: 99%
“…Benefiting from this versatility, squaraines have been extensively used in applications such as solar cells, [171][172][173][174] colorimetric sensing, [175][176] photothermal therapy [177][178] and imaging. [179][180][181] Squaraines whose synthesis has been first reported in 1965 [182] have seen their chemical structures to drastically evolve since these pioneering works and 1,2-and 1,3squaraines, symmetrical and asymmetrically substituted structures can be now selectively prepared. Notably, if the synthesis of 1,3-squaraines is known since decades, the regioselective synthesis of 1,2-squaraines has only been developed in 2011, explaining still the scarcity of the family of squaraines.…”
Section: Type I Photoinitiatorsmentioning
confidence: 99%
“…The strong donation of indolizine allows for the retention of cyanine band structuring when indolizine is used in pentamethine and squaraine core systems. [32][33][34] Recent work from our group has shown that the substitution of amines for indolizine on rhodamine led to a dramatic red-shi of the absorption and emission spectrum with SWIR emission observed. 35 However, the synthesis of the rhodindolizine was challenging and obtaining pure material from the harsh conditions required to open the lactone ring was problematic.…”
Section: Introductionmentioning
confidence: 99%